The Effect of Binder on Bioceramic Surface Roughness when Milling using Ball Nose End Mill - Suleiman, Amin Suffian; Rafai, Noor Hakim (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Nowadays, the increasing number of road accidents has led to a risesince the accidents may result in permanent disability that often requiresurgical intervention. As a purpose to replace bone, a type of bioceramicwhich is hydroxyapatite (HAP) is chosen since it is a chemical substancethat has similar characteristics to the mineral found in human bone andhard tissues. The water-soluble binder is used to make the substanceshold together which is PEG and PVA. Four (4) samples of hydroxyapatitewith different amounts of binder are made to examine the effects ofbinders on the bioceramic mechanical properties. on bioceramic surfaceroughness when milling using ball nose end mill. The sample isprepared by using dry mixing and compaction method whereas theratio of PEG and PVA used are from 1% to 4% by weight. Aftercompaction, the samples are sintered in the furnace for a total of 22hours with 2 hours of soaking period in which the heating and coolingrate is 120 o C/hour. The temperature set for the soaking period is1200 o C. The HAp sintered body is then machined by CNC millingmachine using ball nose end mill cutter with a constant machiningparameter of cutting speed, feed rate and depth of cut which is27m/min, 40mm/rev and 0.1mm. Other than that, the sampleundergoes mechanical properties testing such as modulus of rupture,vickers hardness, porosity and density. From the test, it is observed theamount of binder used influences the mechanical properties and surfaceroughness of the sample. Sample 4 which contains PEG 4 PVA 1 has thehighest yield strength, hardness value and surface roughness. Otherthan that, the highest porosity obtained is sample 3 which contains PEG3 PVA 2 and sample 4 has the highest density. In conclusion, thehydroxyapatite (HAp) samples with different amounts of binder usedinfluence the sample compatibility and mechanical properties.